2016
DOI: 10.1002/bab.1206
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel lichenase from Bacillus licheniformis GZ‐2

Abstract: A novel lichenase from Bacillus licheniformis GZ-2 was purified to homogeneity by two steps ion-exchange chromatography with a specific activity of 8231.3 U/mg. The purified enzyme showed as a single protein band with a molecular mass of 25 kDa. The optimum pH and temperature for the enzyme activity were 6.5 and 60 °C, respectively. The enzyme exhibited strict specificity for β-1,3-1,4-d-glucans. The kinetic parameters Km and Vmax were 5.11 mg/mL and 2097 µmol/Min/mg for lichenan and 7.42 mg/mL and 1440 µmol/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…This result was dissimilar to the activating effect of Mg ++ ions recorded by Jung et al ( 2010 ), Cheng et al ( 2014 ), Zhang et al ( 2017 ) and Schröder et al ( 2018 ). Partial inhibition of the enzyme occurred by high concentration of Ca ++ , while no change in activity observed with low level, similarly to these data slight inhibition with Ca ++ ions was reported by Apiraksakorn et al ( 2008 ), Elgharbi et al ( 2013 ) and Wang et al ( 2014 ) and dissimilarly Ca ++ ions made activation for other β-1,3–1,4-glucanases (Gao 2016 ; Elgharbi et al 2017 ; Bernardi et al 2018 ). Complete inhibition of Halomonas meridiana ES021 β-1,3–1,4-glucanase was also observed with Cu ++ ions, similarly to Yang et al ( 2008 ), Elgharbi et al ( 2013 ) and Pei et al ( 2015 ), this was disagreed with the activating effect reported by Celestino et al ( 2006 ), Wang et al ( 2007 ), Yang et al ( 2014 ) and Niu et al ( 2016b ) for the same metal ion.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This result was dissimilar to the activating effect of Mg ++ ions recorded by Jung et al ( 2010 ), Cheng et al ( 2014 ), Zhang et al ( 2017 ) and Schröder et al ( 2018 ). Partial inhibition of the enzyme occurred by high concentration of Ca ++ , while no change in activity observed with low level, similarly to these data slight inhibition with Ca ++ ions was reported by Apiraksakorn et al ( 2008 ), Elgharbi et al ( 2013 ) and Wang et al ( 2014 ) and dissimilarly Ca ++ ions made activation for other β-1,3–1,4-glucanases (Gao 2016 ; Elgharbi et al 2017 ; Bernardi et al 2018 ). Complete inhibition of Halomonas meridiana ES021 β-1,3–1,4-glucanase was also observed with Cu ++ ions, similarly to Yang et al ( 2008 ), Elgharbi et al ( 2013 ) and Pei et al ( 2015 ), this was disagreed with the activating effect reported by Celestino et al ( 2006 ), Wang et al ( 2007 ), Yang et al ( 2014 ) and Niu et al ( 2016b ) for the same metal ion.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast with these results some investigators reported an inhibitory effect of Co ++ ions on β-1,3–1,4-glucanase (Chaari et al 2012 ; Elgharbi et al 2013 ; Chaari et al 2014 ; Wang et al 2014 ; Elgharbi et al 2017 ; Ali et al 2019 ). The enzyme was also slightly activated in presence of Mn ++ , this result agreed with the data reported by (Teng et al 2007 ; Kim et al 2014 ; Yan et al 2018 ), while disagreed with (Wang et al 2007 ; Apiraksakorn et al 2008 ; Hong et al 2009 ; Luo et al 2014 ; Pei et al 2015 ; Gao 2016 ) who reported partial inhibition effect of Mn ++ ions while complete inhibition of the enzyme was reported by (Yang et al 2008 ; Elgharbi et al 2013 ; Chaari et al 2014 ; Kim et al 2014 ; Elgharbi et al 2017 ).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…(II) Since the organisms live on organic matter they are evolved for high concentrations of nutrient supply which enables the them to reach high cell densities in fermentations 7 . Finally, (III) they secrete high amounts of many efficient bio-polymer hydrolases 8 like lichenases 9 , lipases 10 , thermostable alpha-amylases 11 , and many more 1220 . Exoproteases of the subtilisin Carlsberg family are an industrial fermentation product of B .…”
Section: Introductionmentioning
confidence: 99%